A Brief Review of Pulp and Froth Rheology in Mineral Flotation - Lei Wang; Chao Li (Journal of Chemistry)
In mineral flotation, rheological problems have limited the efficient upgrading of low-grade and complex ores. Since pulp and froth rheology are deemed to play different roles in influencing the separation performance, in this paper, a brief review on pulp and froth rheology in flotation is provided, with an objective of developing a basic understanding of rheology in flotation. The essential variables that affect the rheology of a flotation pulp and froth are discussed. The methods for measuring pulp and froth rheology are presented. The correlations of pulp and froth rheological properties to flotation performance are reviewed. Strategies that are currently used to mitigate the deleterious effects of problematic ores in flotation are also provided for flotation optimization. Research gaps are also proposed to highlight the need of further exploration of flotation rheology in future.